Toxicity test of bioceramic biphasic calcium phospate (BCP) Sr-Ag doping as bone graft in BHK-21 fibroblast cells - Wahjuningrum, Dian Agustin; Setyabudi, Setyabudi; Chusnita, Ria (Conservative Dentistry Journal, 2023)
Background: Bone graft is a substitute material that is used to assist reconstruction, stabilize the structure and bonds in bone, stimulate the osteogenesis process and as a healing bone defect. One type of bone graft that has good osteoinductive and bicompatibility is alloplast which is a synthetic calcium phosphate compound. The most frequently used Calcium Phosphate groups are Hydroxyapatite (HA), β-Tricalcium Phosphate (β-TCP), and Biphasic Calcium Phosphate (BCP). In this study the material used was BCP doping Sr2+ and Ag+. Strontium ions (Sr2+) can increase osteoblast activity, reduce osteoclast activity and cytokine production, improve osteointegration, and minimize fractures. Ag+ ion has the ability as an antibacterial agent. Purpose: To explain and prove the toxicity of bioceramic Biphasic Calcium Phosphate (BCP) doped Sr-Ag as bone graft on BHK-21 fibroblast cells. Methods: This type of research is a laboratory experiment with a post-test only control group design. Treatment with Biphasic Calcium Phosphate (BCP) doped Sr-Ag with concentrations of 200 ppm, 180 ppm, 160 ppm, 140 ppm, 120 ppm, 80 ppm, 40 ppm, 20 ppm, 10 ppm, 5 pmm, 2.5 ppm, 1.25 ppm, 0.625 ppm in BHK-21 fibroblast cell culture. Results: The percentage of fibroblast cell life at concentrations of 200 ppm, 180 ppm, 160 ppm, 140 ppm, 120 ppm, 80 ppm, 40 ppm, 20 ppm, 10 ppm, 5 pmm, 2.5 ppm, 1.25 ppm, 0.625 ppm, respectively, the percentage of live cells was 38% 44%, 46%, 50%, 52%, 65%, 69%, 71%, 72%, 75%, 77%, 81%, and 87%. The parameter used in this toxicity test is CD50. Conclusion: The results of the toxicity test of bioceramic Biphasic Calcium Phosphate (BCP) doped Sr-Ag as a bone graft showed a toxic and non-toxic effect on BHK-21 fibroblast cells at certain concentrations.